Factors associated with persistent anti-desmoglein positivity after remission in pemphigus vulgaris: a prospective registry-based cohort study - Zhou, Yuxi; Wang, Yiyi; Wang, Mi; Zhou, Xingli; Luo, Limei; Yan, Wei; Li, Wei (Frontiers in Immunology, 2025)
IntroductionAnti-desmoglein (Dsg) antibodies are well-established markers correlated with clinical phenotype and disease severity in pemphigus vulgaris (PV). However, elevated anti-Dsg antibody levels have been observed in some patients during clinical remission (CR). This study aimed to identify clinical characteristics and risk factors in PV patients with elevated anti-Dsg antibodies after achieving CR.MethodsWe conducted a cohort study based on the prospective registry database of autoimmune bullous diseases patients at West China Hospital between April 2016 and March 2022. PV patients with at least 12 months of follow-up were enrolled. The pemphigus disease area index (PDAI) and anti-Dsg antibody titers were measured at baseline and 1, 3, 6, 9, 12 months during follow-up. Univariate, multivariate analyses and receiver operating characteristics (ROC) curves were performed to identify associated factors with persistent antibody positivity and optimal cut-off values respectively. The primary outcome was the persistent positivity of antibodies against Dsg after achieving CR.ResultsAmong 239 PV patients enrolled in this study, 118 (49%) achieved CR. Cataracts were identified as an independent risk factor for persistent anti-Dsg1 positivity after CR. Higher baseline anti-Dsg3 antibody titers and PDAI scores were significant predictors of increased anti-Dsg3 levels post-CR, with gender also being a contributing factor. ROC analysis determined a cut-off value of 157.4 U/mL for anti-Dsg3 with 56.3% sensitivity and 82.6% specificity.ConclusionThe presence of Cataracts may indicate persistent anti-Dsg1 positivity after CR, while elevated anti-Dsg3 titers and PDAI scores at baseline may predict sustained elevated anti-Dsg3 post-CR.